GAMBARAN DEPRESI PADA PASIEN DENGAN HEMODIALISIS - Nia Agustiningsih (Jurnal Kesehatan Mesencephalon, 2018)
Abstract : Patients with chronic renal failure who undergo hemodialysis need to get attention not only on physiological issues but also psychological problems. This study aims to determine the picture of depression in patients with hemodialysis. This research uses descriptive research design. The number of respondents in this study 30 respondents obtained by using purposive sampling technique. The research was conducted in unit hemodialysis RS Wava Husada Kepanjen from 21 to 23 April 2017. The instrument used to determine depression is Beck Depression Inventor questionnaire The results obtained that there is low depression 15 people (50%), moderate depression 10 people (33,3 %), severe depression 4 people (13,3%) and very heavy depression 1 person (3,4%). It is recommended that health services in providing hemodialysis therapy in patients with chronic renal failure should not only focus on the physiological condition of the patient but also need to pay attention to the patient's psychological condition. Key Word : Depression, Hemodialysis Patient Abstrak : Pasien gagal ginjal kronis yang menjalani hemodialisis perlu mendapatkan perhatian tidak hanya pada masalah fisiologis namun juga masalah psikologis. Penelitian ini bertujuan untuk mengetahui gambaran depresi pada pasien dengan hemodialisis.Penelitian ini menggunakan desain penelitian deskriptif. Jumlah responden dalam penelitian ini 30 responden yang didapatkan dengan menggunakan tehnik purposive sampling. Penelitian dilakukan di unit hemodialisis RS Wava Husada Kepanjen mulai tanggal 21 – 22 April 2017.Instrumen yang digunakan untuk mengetahui depresi adalah kuesioner Beck Depression Inventor Hasil penelitian didapatkan bahwa terdapat depresi rendah 15 orang (50%), depresi sedang 10 orang (33,3%), depresi berat 4 orang (13,3%) dan depresi sangat berat 1 orang (3,4%). Sebaiknya pelayanan kesehatan dalam memberikan terapi hemodialisis pada pasien dengan gagal ginjal kronis sebaiknya tidak hanya fokus pada kondisi fisiologis pasien namun juga perlu memperhatikan kondisi psikologis pasien. Kata Kunci : Depresi, Pasien Hemodialisis